Reactive power optimization system of distribution network based on edge calculation. Issue 1 (May 2021) - Huang, Jinbo; Fang, Jiangxiao; Hu, Liexiang; Shi, Bolong; Li, Suirong; Tu, Yiyan
Abstract: To deal with the adjustment difficulties caused by the access of photovoltaic (PV) in distribution network, this paper introduces a reactive power optimization system of distribution network based on edge calculation. The proposed system includes two parts. Firstly, the distribution PV edge nodes based on edge calculation are carefully designed. Secondly, based on the edge nodes, the PV station, the grid reactive power optimization, the Automatic Voltage Control (AVC) centre, and the distribution photovoltaic power reactive voltage are controlled co-ordinately. The simulation results prove that the proposed system can effectively improve the voltage quality and the voltage regulation ability of distribution network.